2018
DOI: 10.1371/journal.pone.0206854
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical study of Primo-Lacto: A closed system for colostrum collection

Abstract: BackgroundColostrum is the first nutritional liquid that comes out of the breast during lactation. Colostrum collection can be challenging due to the small volume produced, and because breast pumps are not designed for colostrum collection. Besides pumping colostrum, the generally accepted practice is to use any available container to hand-express colostrum. Transfer between containers may lead to contamination, higher chance of infection and loss of colostrum. Our aim was to understand if a dedicated colostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The newborn, especially if preterm, has an underdeveloped innate and adaptive immune system with a consequent increase in susceptibility to infection [4,5]. Early breastfeeding provides those immunomodulant compounds which can act as a support at birth for preventing immediate risks of infections and diseases, while driving towards improving the off-spring's immune system and establishing tolerance with a decreasing risk of developing allergic diseases [2][3][4][5][6]. This review highlights how most of the immune components, particularly antiinflammatory and anti-allergic elements, are more represented in colostrum than in transitional/mature milk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The newborn, especially if preterm, has an underdeveloped innate and adaptive immune system with a consequent increase in susceptibility to infection [4,5]. Early breastfeeding provides those immunomodulant compounds which can act as a support at birth for preventing immediate risks of infections and diseases, while driving towards improving the off-spring's immune system and establishing tolerance with a decreasing risk of developing allergic diseases [2][3][4][5][6]. This review highlights how most of the immune components, particularly antiinflammatory and anti-allergic elements, are more represented in colostrum than in transitional/mature milk.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23]25,32]. Moreover, new evidence demonstrated that oral colostrum priming improves immune protection and reduces the time to full enteral feeding in preterm infants [5,51,52]. Nevertheless, difficulties in nourishing with colostrum, which has an inverse rate between richness of immune components and volume, are extremely common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are 184 premature newborn deaths per day, or 8 premature neonatal deaths every hour. (Kristensen-Cabrera et al, 2018) The results of research conducted by Steve Harakah (2020) in Jeddah explained that colostrum is yellow, thick, and sticky. Some mothers still think colostrum is a disease and is not safe for consumption by babies.…”
Section: Introductionmentioning
confidence: 99%